2008
DOI: 10.1104/pp.107.111286
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Expression Profiling Arabidopsis at the Stage ofGolovinomyces cichoracearumHaustorium Formation    

Abstract: (T.S., K.D.)Compatibility between plants and obligate biotrophic fungi requires fungal mechanisms for efficiently obtaining nutrients and counteracting plant defenses under conditions that are expected to induce changes in the host transcriptome. A key step in the proliferation of biotrophic fungi is haustorium differentiation. Here we analyzed global gene expression patterns in Arabidopsis thaliana leaves during the formation of haustoria by Golovinomyces cichoracearum. At this time, the endogenous levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 81 publications
1
74
0
1
Order By: Relevance
“…interaction between Arabidopsis and G. cichoracearum, revealed that host photosynthesis is likely stimulated by the fungus, through the induction of genes involved in chlorophyll binding and chlorophyll a oxygenase (Fabro et al, 2008). Though it is conceivable that an increase in photosynthetic rate is required, as the metabolic demands of the infected epidermal tissue increase, these findings are somewhat contradictory to those obtained in the study of Zimmerli et al (2004).…”
Section: The Ups and Downs Of Gene Expression: Transcriptional Changementioning
confidence: 80%
See 1 more Smart Citation
“…interaction between Arabidopsis and G. cichoracearum, revealed that host photosynthesis is likely stimulated by the fungus, through the induction of genes involved in chlorophyll binding and chlorophyll a oxygenase (Fabro et al, 2008). Though it is conceivable that an increase in photosynthetic rate is required, as the metabolic demands of the infected epidermal tissue increase, these findings are somewhat contradictory to those obtained in the study of Zimmerli et al (2004).…”
Section: The Ups and Downs Of Gene Expression: Transcriptional Changementioning
confidence: 80%
“…The broad range of transcriptional changes that occur in Arabidopsis during powdery mildew infection , Fabro et al, 2008 reflect both defense responses mounted by the plant as well as possible manipulation of the host by the fun-gal pathogen. With the sequencing of the Arabidopsis genome and availability of novel technologies for transcript profiling (oligonucleotide-based microarray chips) it has been possible to peek into the gene expression changes that occur during the infection process.…”
Section: The Ups and Downs Of Gene Expression: Transcriptional Changementioning
confidence: 99%
“…The primary functions of gene products encoded by these loci were abiotic and biotic stress responses. All five loci have putative orthologs in Arabidopsis that are responsive to abscisic (ABA) or jasmonic (JA) acid, two plant hormones with well-documented correlations to abiotic stress responses (Glazebrook et al 2003;Wong et al 2006;Wasternack 2007;Fabro et al 2008;Mizuno and Yamashino 2008). In addition, gene expression for four of the five loci in f P-values listed in boldface type are also significant using a Bonferroni correction.…”
Section: Discussionmentioning
confidence: 99%
“…TFs often exhibit low-level and highly localized expression changes; therefore, we expected our site-specific expression analysis to identify unique TFs with important functional roles in the PM interaction. We found 67 TFs exhibited altered expression at the site of infection, with 79% not previously associated with a compatible PM interaction (4,(7)(8)(9). Although many of these PM site-specific TFs have no defined function, we identified sets of TFs associated with the following processes: photosynthesis, drought/cold tolerance, pathogen defense and cell death, auxin signaling/response, and the cell cycle (Fig.…”
Section: Site-specific Profiling Identifies Previously Hidden Localizmentioning
confidence: 94%